Diversitas Metodologi Syarah Hadis di Indonesia Awal Abad ke-20: Studi atas Karya Mahfuẓ al-Turmusī dan Kasyful Anwar al-Banjarī - Munirah (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2023)
The tradition of hadith in Indonesia is an important intellectual heritage that reflects the dynamics of local Islamic thought. However, in-depth studies of the methodology of hadith syarah by Nusantara scholars, especially in the early 20th century, are still rare. This study aims to analyze the methods and characteristics of hadith narration in two important works: al-Khil'ah al-Fikriyyah by Muhammad Mahfūẓ al-Turmusī and al-Tabyīn al-Rāwī by Kashful Anwar al-Banjarī. This research uses a qualitative approach based on literature studies, with the sociological theory of Karl Mannheim's knowledge as the framework of analysis, as well as hermeneutic methods in reading texts. Research shows that Mahfūẓ uses the taḥlīlī method with a linguistic approach and academic systematics, including sanad analysis, sentence structure, to the dimensions of logic and balaghah. Meanwhile, Kashful Anwar uses the communicative and populist method of ijmālī, based on the content of moral messages and religious practices, and enriched by fiqh and Sufism. Both of them studied Arba'īn Nawawī, but with different styles and orientations. This difference is due to the audience factor that each faces; Mahfūẓ targets students and scientists, while Kashful targets the general public of Banjar. These findings confirm that the method of hadith syarah in Indonesia is contextual, flexible, and integrated with the social reality of the ummah. This tradition also shows the intellectual independence of Nusantara scholars in developing Islamic scientific treasures in a creative and relevant manner. .